Factors associated with the prevalence of postpartum anxiety disorder and depression in Syrian Migrant women living in Turkey: A cross-sectional study - Atak, Muhammed; Sezerol, Mehmet Akif; Değer, Mehmet Sait; Kurubal, Hamza (MDPI, 2023)
The global migration trend has brought attention to the mental health of immigrant populations, especially postpartum women. The prevalence of postpartum anxiety and depression among these populations remains a growing concern. This study aimed to explore the factors associated with postpartum anxiety and depression among immigrant women, with a special emphasis on Syrian migrants in Turkey. A cross-sectional design was employed, enrolling postpartum women who visited the Strengthened Migrant Health Center in Istanbul between July and December 2022. Data were collected using a three-part questionnaire comprising sociodemographic details and scores from the Edinburgh Postpartum Depression Scale (EPDS) and Beck Anxiety Scale (BAI). The average age of participants was 25.73 years. The mean EPDS and BAI scores were low at 1.27 and 3.85, respectively. Notably, 97.1% of women scored below the EPDS cut-off point of 13. EPDS scores showed a significant relationship between income levels and COVID-19 vaccination status, while BAI scores were significantly associated with educational levels. There was an inverse correlation between EPDS scores and the number of cohabitants in a household. The observed low rates of postpartum depression and anxiety could be attributed to the accessible health services and psychosocial support for immigrants in Turkey. It would be useful to conduct multicenter and comprehensive epidemiological studies on migrant puerperas.
Keywords: Immigrant; Postpartum; Postpartum Anxiety; Postpartum Depression; Maternal Health; Perinatal Healthcare